Extra-Planar gas in the Leiden/Argentine/Bonn HI Surveys - Kalberla, P. M. W. (2005)
We present a novel approach for a definition of the phase space of the Milky Way HI disk and its associated gaseous halo. We discuss how model and observations can be used to discriminate between disk, disk-halo interface and the more distant halo. The model is applied to the new LAB galactic 21-cm line survey, a joint Leiden/Argentine/Bonn project. This new all-sky survey merges an updated version of the Leiden/Dwingeloo (LDS) survey with southern sky observations from the Instituto Argentino de Radioastronomìa (IAR). The survey was processed in Bonn and is essentially free from stray radiation and spurious instrumental effects. These data give evidence that the cloudy HI disk-halo interface, detected recently by tetLockman02 in the inner Galaxy at R ∼ 5 kpc is rather extended. The LAB survey shows numerous prominent filaments and cloudy features that stand out clearly against the Galactic disk reaching distances R ∼ 20 kpc, z ∼ 7 kpc. One particular interesting region at R ∼ 14 kpc, z ∼ 4 kpc was mapped with the Effelsberg telescope. We find isolated cold HI clumps with properties very similar to those in the inner Galaxy. High velocity clouds populate the most distant part in the Milky Way phase space. Compact high column density features are found to be surrounded by diffuse low column density envelopes. Their lower phase space distance suggests some interaction with the Milky Way.